Nonlinear Quantum Dot Light Emitting Diode Dynamics and Synchronization with Optoelectronic Feedback - Methag Abdalwahed Kadim; Ajeel, Sadeq; Ali Natheer Tuaimah; Ali Falah Hassan; F. Abdalah, Sora; Al naimee, Kais; Meucci, Riccardo; Alkhursan, Amin; Ali. H. Khidhir; ALHusseini, Hussein (مجلة علوم ذي قار, 2023)
We studies a three-variable dimensionless model for a quantum dot light emitting diode (QD-LED) subject to optoelectronic feedback (OEFB). In dependence of the feedback strength and delay-time we analyze complex bifurcation scenarios for the intensity of the emitted light as well as time series, fast Fourier translate (FFT) and phase plane of all dynamic variables in order to elucidate the dynamics of the light emitting diode. The chaotic dynamic is completely determined by both the variation of the OEFB strength and delay-time of the QD-LED, as evidenced by bifurcation diagram. Our results show that small delay time lead to repeat periodicity of the light emitting towards OEFB. Furthermore, we study chaos synchronization of two QD-LED which are coupled via a unidirectional and bidirectional coupling system. When periodic systems are non-identical, both unidirectional and bidirectional systems depending on the coupling strength parameter the system exhibits completely synchronization. Residual chaos, the mean coherence and entropy are discussed as well.